The Handbook of Salutogenesis - Mittelmark, Maurice B.; Sagy, Shifra; Eriksson, Monica; Bauer, Georg F.; Pelikan, Jürgen M.; Lindström, Bengt; Espnes, Geir Arild (Springer Nature, 2017)
Health Promotion and Disease Prevention; Medical Sociology; Health Psychology